STRATEGY FOR PREVENTING DRUG ABUSE AMONG ADOLESCENTS BY THE NATIONAL UNITY AND POLITICS AGENCY OF SOUTH LABUHANBATU REGENCY - Nani Chairani Lestari Lubis; Tengku Irmayani; Agus Suriadi (Universitas Negeri Medan, 2026)
This research aims to describe and analyze strategies for preventing narcotics abuse by the South Labuhanbatu Regency National and Political Unity Agency (Bakesbangpol) and identify obstacles in its implementation. The main problem addressed by this research is that South Labuhanbatu Regency ranks among the top five areas in North Sumatra Province for narcotics danger, with 371 suspects reported between 2023 and October 2024, primarily from the productive age group and teenagers. The research method used is a descriptive qualitative approach. Data collection techniques were carried out through triangulation, which included semi-structured interviews with key informants, observation, and documentation studies.